The effect of applying quality in examining bodies in forensic medicine in Mecca - Ahmed.A.Alsulami; Riyan.K.Qasim; Hani.S.Mujalid; Ghaday.A.Zaylee; Ahmad.H.Alquerashi; Alaa.M.Saif; Naif.J.Alazahrani; Mohana.A.Alsolimy; Amin.A.Ali; Faisal.F.Algethami; Mohammed abdulfattah sindy (International Journal of Medical Toxicology and Legal Medicine, 2024)
This current study aims to know the impact of applying quality standards in examining dead bodies in forensic medicine in Mecca, and the impact of employees applying quality standards at work. The questionnaire was prepared via Google Drive and distributed to all employees of the Forensic Medical Services Center in Mecca (administrators, technicians, and doctors). The questionnaire was distributed to them via the social networking program (WhatsApp), and responses were obtained via email. It concluded that Quality is applied to the examination of corpses at a high rate of up to 80%, and thus the place is considered to be highly compliant with quality standards.